Safflower extract (Carthamus tinctorius Linn.) suppresses proinflammatory cytokines level in rheumatoid arthritis mice model stimulated by complete Freund’s adjuvants - Adryan Fristiohady, Taifo Mahmud, Jia Tuan Maming, Arfan Arfan, Asriullah Jabbar, Muhammad Ilyas Yusuf, La Ode Muhammad Julian Purnama, Lidya Agriningsih Haruna, Wirhamsah Al Ramadan, Wahyuni Wahyuni, Rini Hamsidi, Rathapon Asasutjarit, Idin Sahidin (Journal of Applied Pharmaceutical Science, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by inflammation of the synovial membrane, and swelling, associated with excessive production of proinflammatory cytokines. In addition, anti-citrullinated protein antibodies is excessively high in RA. Carthamus tinctorius Linn. (C. tinctorius), commonly known as Safflower, is widely used as traditional medicine in Indonesia and has anti-inflammatory properties. This study aims to determine cell viability on HEK293 cells and the anti-RA activity of the ethanol extract of C. tinctorius on reducing edema in animal models of RA mice and to determine the anti-RA activity ethanol extract C. tinctorius against rheumatoid factor (RF) in RA mice. In this study, HEK293 cell line was treated with C. tinctorius extract at various concentrations. In addition, mice’s paws were examined after being injected with complete Freund’s adjuvant (CFA) as an intraplantar RA inducer and treated with 2.5 mg/kg body weight (BW) of methotrexate, and extract C. tinctorius at various concentrations orally once a day for 14 days. Then, the paw’s thickness was measured using a gauge meter, arthritis index scoring was observed daily, and agglutination in the RF test was observed on the 17th and 31st days. The collected data was analyzed using one-way analysis of variance. Moreover, an In-Silico test was carried out by measuring the affinity and stability of C.tintorius extract as an anti-RA agent against the cytokines IL-1β and tumor necrosis factor-alpha. The test results showed C. tinctorius at various concentrations were safe to HEK293 cell lines and the administration of C. tintorius extract at 100, 200, and 400 mg/kg BW doses could reduce paw thickness, arthritis index scoring >1, and no agglutination occurred in the RF test. It can concluded that the C. tintorius extract is safe to HEK293 and has activity against CFA-induced RA.
Keywords: Carthamus tinctorius, cell viability, anti-rheumatoid, in silico